MEDB-46. ONC201 affects Group 3 Medulloblastoma growth by impairing cancer stem cells. (3rd June 2022) - Abballe, Luana; Antonacci, Celeste; Gianesello, Matteo; Lago, Chiara; Nazio, Francesca; Mastronuzzi, Angela; Catanzaro, Giuseppina; Giannatale, Angela Di; Tiberi, Luca; Locatelli, Franco; Miele, Evelina
Abstract: Cancer stem cells (CSCs) represent a sub-population of cancer cells capable of proliferating and generating heterogeneous cancer cell types. Acquisition of stemness features may represent a strong advantage for neoplastic cells to promote tumorigenesis and progression, driving resistance to conventional therapy and promoting disease relapse. CSCs have been discovered and isolated in major pediatric brain tumors, including medulloblastoma (MB), the most common solid malignancy in childhood. The unfolded protein response (UPR) represents an adaptation mechanism to metabolic obstacles in CSCs, able to increase tumor aggressiveness. The initial activation of the UPR is cytoprotective but the acute activation led to cell death. We found that UPR is active in MB stem cells (MBSC) and particularly in group 3 (G3). ONC201 is an imipridone compound that activates p53-independent apoptosis causing changes in gene expression similar to those caused by UPR. Here, we aim to test the in vitro efficacy of ONC201 on G3 MBSC. We selected 4 G3 MBSC (D341-Med, D283-Med, Med411, and CHLA-01-Med), for the in vitro study. Cells were choosen for their "fidelity" to the MB subgroup through the analysis of global methylation profiling, were grown in stemness conditions and expressed stemness markers at high levels. We investigated the efficacy of ONC201 treatment on CSC features, by evaluating cell viability, cell death, protein synthesis, self-renewal, and cell cycle. ONC201 treatment on G3 MB cells led to an upregulation of ATF4, a key molecule of the UPR, and the induction was stronger in MB cultured in a "stem-like" medium. Moreover, in the most MBSC analyzed, ONC201 was effective against CSCs whether by reduced cell viability, protein synthesis, and self-renewal. We also observed a trend of increased cell death. Our results suggest that ONC201 is potentially effective in treating G3 MB by compromising the stem cell compartment, and thus deserving further investigations.